2014
DOI: 10.1155/2014/792102
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Magnetic Properties of Fe Doped ZnO Nanoparticles Obtained by Hydrothermal Synthesis

Abstract: Diluted magnetic semiconductorsZn1-xFexOnanoparticles with different doping concentration (x=0, 0.01, 0.05, 0.10, and 0.20) were successfully synthesized by hydrothermal method. The crystal structure, morphology, and optical and magnetic properties of the samples were characterized by X-ray diffraction (XRD), energy dispersive spectrometer (EDS), high-resolution transmission electron microscopy (HRTEM), Raman scattering spectra (Raman), photoluminescence spectra (PL), and the vibrating sample magnetometer (VSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…The lattice constants of the doped ZnS are smaller than that of pure ZnS, and the lattice constants and and their interplanar distance of doped ZnS decrease with the increase of Cr doped content, reaching minimum for 3% Cr. It can be attributed that the ionic radius of the Cr 3+ (0.69Å) is smaller than that of the Zn 2+ (0.74Å), which revealed that Cr ions occupy Zn ions sites in the wurtzite structure, causing lattice distortion [20].…”
Section: Resultsmentioning
confidence: 99%
“…The lattice constants of the doped ZnS are smaller than that of pure ZnS, and the lattice constants and and their interplanar distance of doped ZnS decrease with the increase of Cr doped content, reaching minimum for 3% Cr. It can be attributed that the ionic radius of the Cr 3+ (0.69Å) is smaller than that of the Zn 2+ (0.74Å), which revealed that Cr ions occupy Zn ions sites in the wurtzite structure, causing lattice distortion [20].…”
Section: Resultsmentioning
confidence: 99%
“…This mode was shifted to a higher number. It might due to the increase of the stress or defect in the ZnO crystal [38]. Moreover, I D /I G ratio of the CS increased to be 0.91 (ZnO-coated CS) and 0.88 (CS-coated ZnO) after being composited with ZnO.…”
Section: Methodsmentioning
confidence: 98%
“…The magnetic properties of these materials depend strongly on the synthesis method, conditions of preparations, etc. They may exhibit room temperature ferromagnetism (RTFM) [1][2][3], spin-glass behavior [4], superparamagnetic properties [5], and the Curie-Weiss paramagnetism with dominating antiferromagnetic interactions [6]. Due to the poor reproducibility by using different preparation methods or the poor resolutions of the commonly used structural characterization techniques, there are many different interpretation of the origin of magnetism in DMSs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the poor reproducibility by using different preparation methods or the poor resolutions of the commonly used structural characterization techniques, there are many different interpretation of the origin of magnetism in DMSs. For example, the observed in these compounds RTFM very often is explained by defects; on the other hand, nanosized inclusions of magnetic oxides or metals are usually responsible for the ferromagnetic behavior of the material [1][2][3].…”
Section: Introductionmentioning
confidence: 99%